BIODIVERSITY AND UTILITY OF HERBAL DRUGS IN INDIAN CONTEXT - Kokate, C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
According to Global Biodiversity Assessment estimate of UNEP, the total number of living species across the globe are in the range of 13 to 14 million, of which only 1.75 million species have been scientifically described and documented. Around 20,000 plant species are believed to be used medicinally in third world countries, of which around 8,000 species are systematically utilized traditionally in India. Endowed with a wide diversity of agroclimatic conditions, India is virtually the Botanical Garden of the World. It is one of the top twelve mega diversity countries in the world. Out of eighteen hot spots of biodiversity identified across the globe, India has two located in Eastern Himalaya and Western Ghat regions containing approximately 3500 and 1600 medicinal plants respectively. Under the agreement of G-15 countries, the Department of Biotechnology in India has established three gene-banks for medicinal and aromatic plants which utilize conservation strategies to protect and nurture plants in their native eco-systems (in-situ) or away from their natural habitat (ex-situ). Ayurveda- the Ancient Science of Life – is a time tested traditional system of medicine practiced in India since time immemorial. In past two decades, it has undergone rapid metamorphosis in terms of quality control, safety, efficacy and clinical validations. Herbal medicines derived from Ashwagandha, Punarnava, Brahmi, Isabgol, Tulsi, Turmeric, Neem, Safed Musli, Amla, Shatavari, Garlic, Senna, Tamala, Nutmeg, Shankhapushpi, etc., have revolutionalized modern herbal therapy in India.